2012
DOI: 10.1128/jcm.01231-12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of a Type-Specific Real-Time Quantitative Human Papillomavirus PCR against the Performance of Hybrid Capture 2 for the Purpose of Cervical Cancer Screening

Abstract: cTo be acceptable for use in cervical cancer screening, a new assay that detects DNA of high-risk human papillomavirus (hrHPV) types must demonstrate high reproducibility and performance not inferior to that of a clinically validated HPV test. In the present study, a real-time quantitative PCR (qPCR) assay targeting the E6 and E7 genes of hrHPV was compared with Hybrid Capture 2 (hc2) in a Belgian cervical cancer screening setting. In women >30 years old, the sensitivity and specificity for intraepithelial neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 28 publications
2
56
0
Order By: Relevance
“…both showing a percentage of agreement with a lower confidence bound not less than 87% (kappa value of at least 0.5)) [4]. Recently a number of different molecular HPV test methods have been subjected to this test criterion and it has become the de facto standard by which new tests are assessed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…both showing a percentage of agreement with a lower confidence bound not less than 87% (kappa value of at least 0.5)) [4]. Recently a number of different molecular HPV test methods have been subjected to this test criterion and it has become the de facto standard by which new tests are assessed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The Hybrid Capture 2 (HC2; Qiagen, Hilden, Germany) assay (2-4) and GP5ϩ/6ϩ PCR-based enzyme immunoassay (EIA) kit HPV GP HR (EIA; Diassay, Rijswijk, the Netherlands) (5-9) were the first HPV tests to be clinically validated for primary screening on the basis of longitudinal results from large screening studies (10). Testing for high-risk HPV (hrHPV) nucleic acids is also useful for triage of women with equivocal or mildly abnormal cytology for colposcopy and as a test of cure of treatment (10).Several novel HPV tests have been fully or partially validated by showing noninferiority to HC2 or EIA and high reproducibility (11), as has been extensively reviewed by Arbyn et al (10) and reported in additional studies (12)(13)(14). These tests usually detect around 14 hrHPVs in aggregate, but some provide concurrent (partial) genotype-specific information.…”
mentioning
confidence: 99%
“…Several novel HPV tests have been fully or partially validated by showing noninferiority to HC2 or EIA and high reproducibility (11), as has been extensively reviewed by Arbyn et al (10) and reported in additional studies (12)(13)(14). These tests usually detect around 14 hrHPVs in aggregate, but some provide concurrent (partial) genotype-specific information.…”
mentioning
confidence: 99%
“…Intralaboratory testing took place at the AML laboratory (Antwerp, Belgium) and interlaboratory testing took place between AML and the laboratory of the University Hospital of Ghent (Ghent, Belgium). A total of 510 samples collated at the AML laboratory, which had previously been tested with an in-house multiplex real-time PCR (15,16), were assessed. For the validation criteria to be satisfied, the 95% lower confidence bound of both agreements should be Ͼ87%, with a kappa value Ն0.5 (5).…”
Section: Assessment Of Clinical Performance and Comparison With A CLImentioning
confidence: 99%